Individual differences and creative ideation: neuromodulatory signatures of mindset and response inhibition - Khalil, Radwa; Agnoli, Sergio; Mastria, Serena; Kondinska, Angela; Karim, Ahmed A.; Godde, Ben (Frontiers in Neuroscience, 2023)
This study addresses the modulatory role of individual mindset in explaining the relationship between response inhibition (RI) and divergent thinking (DT) using transcranial direct current stimulation (tDCS). Forty undergraduate students (22 male and 18 female), aged between 18 and 23 years (average age = 19 years, SD = 1.48), were recruited. Participants received either anodal tDCS of the right IFG coupled with cathodal tDCS of the left IFG (R + L−; N = 19) or the opposite coupling (R−L+; N = 21). We tested DT performance using the alternative uses task (AUT), measuring participants’ fluency, originality, and flexibility in the response production, as well as participants’ mindsets. Furthermore, we applied a go-no-go task to examine the role of RI before and after stimulating the inferior frontal gyrus (IFG) using tDCS. The results showed that the mindset levels acted as moderators on stimulation conditions and enhanced RI on AUT fluency and flexibility but not originality. Intriguingly, growth mindsets have opposite moderating effects on the change in DT, resulting from the tDCS stimulation of the left and the right IFG, with reduced fluency but enhanced flexibility. Our findings imply that understanding neural modulatory signatures of ideational processes with tDCS strongly benefits from evaluating cognitive status and control functions.